(untitled) (Journal of Science and Technology, 2016)
In this paper, review and research is made on usability testing in the Geo-information environment, as used in modern digital cartographic visualization. Modern Cartography is more than the presentations of geographical information in a map form. Nowadays, it is seen as Geo-visualization, involving the visual exploration of data by an individual scientist as well as the final presentation to a more general public. The increasing use of the Internet and multi-media to disseminate geographical information place their own specific demands on visualization techniques. As a result of these, there is the need to test the efficiency, effectiveness and satisfaction of a visualization tool for the final consumer. The test method in which the paper seeks to address is the ‘think aloud’ method. The paper addresses how usability testing was conducted using the ‘think aloud’ method in testing a prototype application developed for real estate agents in visualizing buildings in 3D environment (using Virtual Reality).